2020
DOI: 10.1002/net.21949
|View full text |Cite
|
Sign up to set email alerts
|

Improved methods to compare distance metrics in networks using uniform random spanning trees (DIMECOST)

Abstract: We consider the network analytics problem of comparing two distance metrics on the same set of n entities. The classical solution to this problem is the Mantel test, which uses permutation testing to accept or reject the null hypothesis that there is “no relationship between the two metrics.” Its computational complexity is n2 times the number of permutations (based on a user supplied parameter). This work makes two contributions: (1) DIMECOSTP, a more efficient hypothesis test based on uniform random spanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…As before, while the CIs using DC-RST differ slightly from those computed using Wilson's algorithm, they still contain the r value calculated by the Mantel Test. This test previously showed that simply choosing random edges from the complete graph does not suffice, as the CIs generated in this example with random edges do not contain the r value calculated by the Mantel Test [2]. [4] The Lp-norm for p ≥ 1 of a vector ⃗ x is a commonly used measure of "distance" in machine learning for clustering, and is defined by To try and address this, we tried implementing step (2) of random-partition() with a parallel shuffling algorithm instead: MergeShuffle [16], which was chosen because of the availability of an implementation that uses OpenMP.…”
Section: Data Set 1: Comparison Of Distance Normsmentioning
confidence: 92%
See 4 more Smart Citations
“…As before, while the CIs using DC-RST differ slightly from those computed using Wilson's algorithm, they still contain the r value calculated by the Mantel Test. This test previously showed that simply choosing random edges from the complete graph does not suffice, as the CIs generated in this example with random edges do not contain the r value calculated by the Mantel Test [2]. [4] The Lp-norm for p ≥ 1 of a vector ⃗ x is a commonly used measure of "distance" in machine learning for clustering, and is defined by To try and address this, we tried implementing step (2) of random-partition() with a parallel shuffling algorithm instead: MergeShuffle [16], which was chosen because of the availability of an implementation that uses OpenMP.…”
Section: Data Set 1: Comparison Of Distance Normsmentioning
confidence: 92%
“…Bourbour et al proposed an algorithm called Dimecost, which uses uniform, random spanning trees instead of matrices [2]. Recall that the distance matrix is equivalent to a weighted, undirected, complete graph on n vertices.…”
Section: Dimecostmentioning
confidence: 99%
See 3 more Smart Citations